Buddha and Buddhism - Wilson, Horace Hayman (Kolkata : Asiatic Society, 1979)
Contributed articles on Buddhist doctrines, sects and Buddhist Pali literature.
Includes bibliographical references.
English and Bengali.
Keywords: Buddhism; Buddhism -- Doctrines